KONSEP KEPEMIMPINAN DALAM ISLAM - direja, Ahmad (EDUKASI: Jurnal Pendidikan Islam, 2014)
Leadership in Islam occupies a very strategic position. Because leadership is an instrument to achieve the lofty ideals of a nation. Namely the creation of a nation that "baldatun thayyibatun wa rabbun ghafur" (the nations good, prosperous and under the protection of Allah). Therefore, Islam put considerable attention to the issue of leadership. Studies of leadership in Islam, the term used is the word caliph, the priest, ulil amr and al-mulk.